Policy Experimentation, Political Competition, and Heterogeneous Beliefs - Antony Millner; Hélène Ollivier; Leo Simon (Center for Economic Studies and ifo Institute (CESifo), 2014)
We consider a two period model in which an incumbent political party chooses the level of a current policy variable unilaterally, but faces competition from a political opponent in the future. Both parties care about voters payoffs, but they have different beliefs about how policy choices will map into future economic outcomes. We show that when the incumbent party can endogenously influence whether learning occurs through its policy choices (policy experimentation), future political competition gives it a new incentive to distort its policies - it manipulates them so as to reduce uncertainty and disagreement in the future, thus avoiding facing competitive elections with an opponent very different from itself. The model thus demonstrates that all incumbents can find it optimal to over experiment', relative to a counter-factual in which they are sure to be in power in both periods. We thus identify an incentive for strategic policy manipulation that does not depend on self-serving behavior by political parties, but rather stems from their differing beliefs about the consequences of their actions.
Keywords: D72; D83; H40; P48; 330; beliefs; learning; political economy